ADULT LEARNERS IN DISTANCE HIGHER EDUCATION - NORICA-FELICIA BUCUR (Challenges of the Knowledge Society, 2012)
This paper attempts at identifying the main features that characterize distance higher education and adult education, respectively, in order to be able to establish to what extent adult learners can fit in distance higher education programs. The historical background of distance learning education, the factors that influence adult learners, and distance learning’s key objectives, effects, issues, advantages, and disadvantages are to be briefly investigated in order to reach the purpose of this paper. Recent developments in Information Technology have led to a new approach to teaching and learning, especially as far as adult learning and distance learning are concerned. Thus, this study will also focus on the consequences of using technology for course design, delivery, and the perception of adult learners participating in distance learning.